Mutual Funds: Your Money, Your Choice... Take Control Now and Build Wealth Wisely - Jones, Charles; Gill, Edwin (Financial Times Prentice Hall books., 2002)
Mutual Funds: Your Money, Your Choice gives you an unvarnished look at both the positives and the negatives of mutual fund investing: the real risks, the real costs, the real tax issues, and the real returns. Simply and clearly, without complicated charts or equations, top investment researcher Charles P. Jones helps you pick the right funds, and introduces brand-new alternatives - including folios, ETFs, and managed accounts - that can help you meet your goals when mutual funds won't.